Optimization of Process Variables in the Synthesis of Tributyl Citrate Using a Polyvinylpolypyrrolidone-Supported Brønsted Acidic Ionic Liquid Catalyst - Song Wang; Lanlan Xu; Linlin Xu; Chengcheng Tian; Yinyan Guan (International Journal of Polymer Science)
A polyvinylpolypyrrolidone- (PVPP-) supported Brønsted acidic ionic liquid catalyst ([BsPVPP]HSO4) was synthesized by the reaction between SO3H-functionalized PVPP and H2SO4. The prepared catalyst was characterized by IR, XRD, FESEM, TG, and DSC. The catalytic activity of [BsPVPP]HSO4 in the preparation of tributyl citrate (TBC) by the esterification reaction between citric acid and n-butanol was investigated. Response surface methodology (RSM) was applied to optimize the process variables of the esterification reaction. The variables, including the reaction time, the n-butanol-to-citric acid mole ratio, the reaction temperature, and the catalyst amount, were optimized by a Box-Behnken design. Under optimized conditions, with a n-butanol-to-citric acid mole ratio of 5.2 : 1 and a reaction temperature of 120°C, the TBC yield reached 92.9% within 5.5 h in the presence of 6.6 wt% of catalyst; this result is in good agreement with the values predicted by the mathematical model. Moreover, the catalyst could be recycled four times with high catalytic activity.